2007
DOI: 10.1590/s0103-64402007000200005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of two self-etching primer systems on enamel adhesion

Abstract: The aim of this study was to compare two self-etching and a total-etch adhesive systems by assessing their shear bond strength to bovine enamel and the microleakage on class V composite restorations prepared on bovine enamel. Bovine teeth selected and allocated in three groups: Group 1: Scothbond Multi-Purpose; Group 2: Clearfil Liner Bond 2V; Group 3: Etch & Prime 3.0. For the microleakage test, each group was composed of ten class V restorations on the buccal surface. Two examiners attributed scores ranging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…This finding was in agreement with those of previous studies 19,22,26) . Several reasons have been advocated to account for the suboptimal performance of self-etch adhesives: (1) the combination of acidic hydrophilic and hydrophobic monomers into a single step may compromise the polymerization of the adhesive; (2) the inherently low strength of the adhesive polymer; and (3) the lower degree of polymerization of the resin monomer due to a major solvent/oxygen inhibition effect during light activation of these materials 27) . Amongst the self-etch adhesives, the results of the present study revealed that AS (a two-step selfetch adhesive) exhibited higher shear bond strength than LP (a one-step self-etch adhesive).…”
Section: Discussionmentioning
confidence: 99%
“…This finding was in agreement with those of previous studies 19,22,26) . Several reasons have been advocated to account for the suboptimal performance of self-etch adhesives: (1) the combination of acidic hydrophilic and hydrophobic monomers into a single step may compromise the polymerization of the adhesive; (2) the inherently low strength of the adhesive polymer; and (3) the lower degree of polymerization of the resin monomer due to a major solvent/oxygen inhibition effect during light activation of these materials 27) . Amongst the self-etch adhesives, the results of the present study revealed that AS (a two-step selfetch adhesive) exhibited higher shear bond strength than LP (a one-step self-etch adhesive).…”
Section: Discussionmentioning
confidence: 99%
“…The most common method to evaluate adhesive properties of restorative materials is bond strength assessment. This has become a well-recognized method to analyze an important part of the in vitro performance of materials (14,15). So the shear bond strength test has been used in this study to evaluate the adhesive properties of WMTA to composite and compomer restorative materials.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18] Some studies reported that self-etching primer systems performed comparably to that of total-etch adhesive systems. 19 However, in other studies, self-etching adhesives showed greater scales of microleakage than adhesives using conventional phosphoric acid as the etchant. 13,16,[20][21][22] There is some concern that the manufacturers are sacrificing enamel bond strength for self-etching primers.…”
Section: Introductionmentioning
confidence: 88%